Synthesis and characterization of a polyoxometalate-based ionic liquid catalyst for delignification of wood biomass - Ozdokur, K.V. (Springer Verlag, 2016)
Conversion of recalcitrant lignocellulosic biomass to renewable and valuable biopolymers has attracted global interest to build up sustainable societies. Delignification of biomass for separating such biopolymers (e.g., cellulose and lignin) has been used as an efficient process. However, conventional delignification methods suffer from considerable drawbacks and cannot be considered as clean processes. In this study, a new type of polyoxometalate (POM) ionic liquid (IL), (C6N2H11)42Mo132O372 (CH3COO)30(H2O)72.ca 284 H2O (1-ethyl-3-methylimidazolium Mo132O372 (CH3COO)30 (H2O)72.ca 184 H2O) (abbreviated as emimPOM), was synthesized and employed as a catalyst in the delignification of wood biomass. The synthesized emimPOM catalyst was characterized by CNH analysis, Fourier transform infrared spectroscopy, thermogravimetric analysis, and differential scanning calorimetry. The results indicated that the 1-ethyl-3-methylimidazolium emim group was appended to a (NH4)42 Mo132O372(CH3COO)30 (H2O)72.ca 120 H2O POM precursor in which the emim group replaced the ammonium group. The emimPOM catalyst effectively delignified wood in an IL emimOAc (1-ethyl-3-methylimidazolium acetate) system: The lignin content of the produced cellulose-rich material was ca. 7.0Â %, much lower than the 32.0Â % lignin content of the untreated wood biomass. The delignification efficiency was improved by optimizing IL catalyst loading, the IL concentration, and the reaction conditions. This POM-based IL could be used in the delignification of lignocellulosic biomass to isolate cellulose and lignin for further chemical and mechanical processing. Â© 2016, Springer-Verlag Berlin Heidelberg.